The landscape of trauma informed care in community-based HIV service organizations in the United States south. Issue 2 (1st February 2023) - Ali, Samira; Stanton, Megan; McCormick, Katie; Reif, Susan
ABSTRACT: Among people living with HIV, trauma is associated with increased viral loads and obstructed access to HIV care. Trauma-Informed Care (TIC), a SAMHSA Evidence Based Practice, responds to the impact of trauma for service users by focusing on all aspects of service delivery systems and structures. TIC could be potentially lifesaving in regions where HIV rates continue to rise, like the U.S. South. Thus, the purpose of this study is to (1) understand the extent to which HIV service organizations in the U.S. South provide mental health and substance use services and referrals; (2) the extent to which they employ trauma informed care and (3) the barriers of employing trauma informed care. Analyzing quantitative data of 207 organizations, we found that less than a third of organizations provided a trauma informed intervention. Only 44% of organizations had participated in TIC training but 84% expressed interest in TIC training. Organizations who completed TIC training were 10 times more likely than those who did not to report that they implemented at least one trauma informed care strategies. Barriers to TIC implementation included lack of training, capacity, and resources. Building the capacity of organizations to implement TIC will be a key to ending the HIV epidemic.